Corticomedullary Strain Ratio: A Quantitative Marker for Assessment of Renal Allograft Cortical Fibrosis. (1st October 2013) - Gao, Jing; Min, Robert; Hamilton, James; Weitzel, William; Chen, Johnson; Juluru, Krishna; Rubin, Jonathan M.
Abstract : Objectives: To quantitatively assess the correlation between the corticomedullary strain ratio and cortical fibrosis in renal transplants. Methods: Using quasistatic ultrasound elasticity imaging, we prospectively assessed the corticomedullary strain ratio in renal allografts of 33 patients who underwent renal transplant sonography and biopsy. Based on Banff score criteria for renal cortical fibrosis, 33 allografts were divided into 2 groups: group 1 (n = 19), with mild (<25%) fibrosis; and group 2 (n = 14), with moderate (>26%) fibrosis. We used 2‐dimensional speckle‐tracking software to perform offline analysis of cortical and medullary strain induced by external compression by the ultrasound transducer. We then calculated the corticomedullary strain ratio (cortical normalized strain/medullary normalized strain; normalized strain = developed strain/applied strain [deformation from the abdominal wall to the pelvic muscles]). An unpaired 2‐tailed t test was used to determine differences in normalized strain and the strain ratio between the groups. Receiver operating characteristic curve analysis was performed to determine the best strain ratio cutoff value for identifying moderate fibrosis. Results: Normalized strain differed between the cortex and medulla (mean ± SD: group 1, 4.58 ± 2.02 versus 2.58 ± 1.38; P = .002; group 2, 1.71 ± 0.42 versus 2.60 ± 0.87; P = .0011). The strain ratio in group 1 was higher than in group 2 (2.06 ± 1.33 versus 0.70 ± 0.20; P = .0007). The area under the receiver operating characteristic curve was 0.964. The sensitivity and specificity of a strain ratio cutoff value of 0.975 for determining moderate fibrosis were 92.9% and 94.7%, respectively. Conclusions: Strain values vary in different compartments of the kidney. The corticomedullary strain ratio on ultrasound elasticity imaging decreases with increasing renal cortical fibrosis, which makes it potentially useful as a noninvasive quantitative marker for monitoring the progression of fibrosis in renal transplants.